2017
DOI: 10.14423/smj.0000000000000680
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Hospital Employees’ Personal Preparedness and Willingness to Work Following a Disaster

Abstract: Public Health experts warn it is not a question of if but when the next flu pandemic will arrive. Historically, we experience three pandemics each century. Many experts suggest we are already overdue for another pandemic. "Today, many influenza experts, including those at the CDC, consider the threat of a serious influenza pandemic to the US to be high. Although the timing and impact of an influenza pandemic is unpredictable, the occurrence is inevitable and potentially devastating." Dr. Julie Gerberding, Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…Nevertheless, we found that 57–70% of VA employees would like more training to improve their level of preparedness for a disaster, with the highest proportion of employees reporting the need for training related to epidemics and manmade disasters compared to natural disasters. These findings are consistent with other studies which found that healthcare workers are more likely to be willing and able to respond to natural disasters and less likely to be willing and able during infectious outbreaks and radiological or chemical events [ 12 14 , 16 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, we found that 57–70% of VA employees would like more training to improve their level of preparedness for a disaster, with the highest proportion of employees reporting the need for training related to epidemics and manmade disasters compared to natural disasters. These findings are consistent with other studies which found that healthcare workers are more likely to be willing and able to respond to natural disasters and less likely to be willing and able during infectious outbreaks and radiological or chemical events [ 12 14 , 16 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…a specifically defined role for the individual during a disaster) were three to five times more likely to respond during a disaster than those without a specified role [ 2 ], and those with a higher perceived importance of their role in an emergency were also more able and willing to report to work during a disaster [ 15 , 16 ]. Studies have also found that non-clinical healthcare workers were significantly less willing to respond during catastrophic events than their clinical counterparts [ 2 , 13 , 21 , 22 , 34 ]. Since only around three in five non-clinicians considered their role in disaster response to be important compared to a quarter of clinicians, training programs should target non-clinical staff and emphasize their importance when responding to a disaster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to obtain a 100% participation of HCW even though it is vital in case of disasters. Previous studies suggested that between 65% and 97% of HCWs were willing to participate in a natural disaster, and between 54% and 86% in an influenza pandemic 11 16 20 21. The reason for this difference in the levels of willingness between the two types of disasters is due to the great distinction in their nature.…”
Section: Discussionmentioning
confidence: 99%
“…Brice et al, from the University of North Carolina at Chapel Hill, take this a step further by describing the factors that would enable or restrict providers from working during a disaster. 5 Jasper and colleagues, from Thomas Jefferson University in Philadelphia, assess one of the few mandatory, stand-alone disaster medicine courses for medical students in the United States. 6 Finally, Scott and Hutchison, from the Medical University of South Carolina, Charleston, provide perspective regarding the hospital preparedness lessons learned from Hurricane Matthew in 2016.…”
mentioning
confidence: 99%